Impact of ghrelin on body composition and muscle function in a long-term rodent model of critical illness. - Neil E Hill; Kevin G Murphy; Saima Saeed; Rahul Phadke; Darren Chambers; Duncan R Wilson; Stephen J Brett; Mervyn Singer (PLoS ONE)
Background Patients with multiple injuries or sepsis requiring intensive care treatment invariably develop a catabolic state with resultant loss of lean body mass, for which there are currently no effective treatments. Recovery can take months and mortality is high. We hypothesise that treatment with the orexigenic and anti-inflammatory gastric hormone, ghrelin may attenuate the loss of body mass following critical illness and improve recovery. Methods Male Wistar rats received an intraperitoneal injection of the fungal cell wall derivative zymosan to induce a prolonged peritonitis and consequent critical illness. Commencing at 48h after zymosan, animals were randomised to receive a continuous infusion of ghrelin or vehicle control using a pre-implanted subcutaneous osmotic mini-pump, and continued for 10 days. Results Zymosan peritonitis induced significant weight loss and reduced food intake with a nadir at Day 2 and gradual recovery thereafter. Supra-physiologic plasma ghrelin levels were achieved in the treated animals. Ghrelin-treated rats ate more food and gained more body mass than controls. Ghrelin increased adiposity and promoted carbohydrate over fat metabolism, but did not alter total body protein, muscle strength nor muscle morphology. Muscle mass and strength remained significantly reduced in all zymosan-treated animals, even at ten days post-insult. Conclusions Continuous infusion of ghrelin increased body mass and food intake, but did not increase muscle mass nor improve muscle function, in a long-term critical illness recovery model. Further studies with pulsatile ghrelin delivery or additional anabolic stimuli may further clarify the utility of ghrelin in survivors of critical illness.